Two New Frequent Dimorphisms in the Protein S (PROS1) Gene* - Mustafa, Stefan; Pabinger, Ingrid; Mannhalter, Christine (Thrombosis and Haemostasis, 1996)
Two new polymorphisms were identified in the proteinS gene (PR0S1): an intronic T/A-dimorphism (PIPS1) in intron K, and an exonic C/A-dimorphism (PEPS2), located in the 3'untranslated trailer of exon 15. Allelic frequencies of 24% (PIPS 1-A) and 17% (PEPS2-A) respectively, were determined in the normal population. The identification of an intronic and an exonic PR0S1 dimorphism, in addition to the known BstXI dimorphism, enlarges the molecular tool box for gene analysis and transcript quantification in hereditary protein S deficiency. Haplotype analysis showed that variability of both new polymorphisms occurred almost exclusively in the A-allele of the known intragenic BstXI dimorphism. Therefore, PEPS2 and PIPS1 are especially valuable in individuals homozygous for the BstXI A-variant.